Prove That :
![\frac{x { \alpha }^{2} + y \alpha + \gamma }{x \alpha + y + \gamma \ { \alpha }^{2} } = \alpha \frac{x { \alpha }^{2} + y \alpha + \gamma }{x \alpha + y + \gamma \ { \alpha }^{2} } = \alpha](https://tex.z-dn.net/?f=++%5Cfrac%7Bx+%7B+%5Calpha+%7D%5E%7B2%7D+%2B+y+%5Calpha++%2B++%5Cgamma++%7D%7Bx+%5Calpha++%2B+y+%2B++%5Cgamma++%5C+%7B+%5Calpha+%7D%5E%7B2%7D+%7D++%3D++%5Calpha+)
Where x, y and gamma are variables and alpha equals to omega(W).
(W = Complex answers of cube root of 1)
Answers
Answered by
3
Answer:
1.2)
The fact that (1.1) can have, for α1,α2<0, solutions with Reλ>0 therefore leads to the dictum that delayed negative feedback can lead to oscillatory instability.
Similar questions